Managerial Moral Strategies—In Search of a Few Good Principles - Soule, Edward H. (Academy of Management Review, 2002)
The goal of this article is to help managers, students, and scholars contend with moral business problems by urging efforts to develop an adequate “managerial moral strategy.” Integrative social contract theory (ISCT) is arguably the most promising candidate available, but a critical analysis reveals a shortcoming: it lacks sufficient moral content. Alleviating this weakness requires the formulation of the moral principles applicable to management. Doing so will elevate the usefulness and the influence of ISCT and the business ethics enterprise generally.